From vehicular networks to vehicular clouds in smart cities - (:unkn) unknown (Elsevier Inc., 2016)
Vehicular networks are inseparable components of a smart city environment due to several applications that improve the quality of life, safety, and security. Applications of vehicular networks vary from safety applications such as blind spot warning and traffic light violations to entertainment such as streaming media or convenience such as parking space identification. Recently established standards such as IEEE 802.11p and IEEE 1609 help achieve effective communications between vehicles and the infrastructure. However, Vehicular Ad hoc Networks (VANETs) are still considered as one of the challenging forms of wireless communication technologies that complement Intelligent Transportation Systems (ITS) that aim to improve the transportation in cooperation with the Information and Communication Technologies (ICTs). VANETs are specialized form of Mobile Ad hoc Networks (MANETs) but protocols that perform well in MANETs may not be ideal for VANETs due to high mobility, intermittent connectivity and heterogeneity. Cloud computing offers the option to offload local resources to a shared pool and can be an ideal solution for compute-intensive and memory-intensive applications. Hence, the concept of vehicular clouds has been introduced to facilitate VANET applications in a resource efficient way with rapid elasticity and a pay-as-you go business model. This chapter presents a comprehensive survey of VANET applications in smart cities along with challenges, solutions and existing implementations. Furthermore, it introduces the state of the art in vehicular clouds for smart cities following an introduction of various vehicular cloud architectures. Moreover, open issues and future directions are presented to help stimulate future studies in this emerging research field. © 2016 Elsevier Inc.
Keywords: Clustering; Intelligent transportation systems; Smart cities; Vehicular cloud; Vehicular networks; Virtualization